PENGARUH PEMBELAJARAN KOOPERATIF TWO STAY TWO STRAY (TSTS) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS X SMAN 3 TAMBUSAI. - -, Yulianti; Deswita, Hera; Afri, Lusi Eka (Universitas Pasir Pengaraian, 2015)
This research aims to porposed cooperative learning to know the effect Two stay Two Stray ( TSTS ) the results of learning math in X class of SMAN 3 Tambusai. The research was Quasi Experiment.After the data tested in two samples class is then analyzed to test the hypothesis test . before tested analyzed by hyphothesis the firstly is that normality, because test normality is not normal so this test used Mann Whitney U From the analysis of data to obtained zcount value of 4.617 while ttablevalue of 2192 for value of Î± = 0:05 . because value of zcount â¥ztable, it is concluded that there is iporposed cooperative learning to know the effect Two stay Two Stray ( TSTS ) the results of learning math in X class of cooperative learning type Two Stay Two Stray ( TSTS ) the results of learning X SMAN 3 Tambusai.